2018
DOI: 10.1002/chem.201802465
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Selective γ‐C(sp3)−H and γ‐C(sp2)−H Arylation of Free Amino Esters Promoted by a Catalytic Transient Directing Group

Abstract: The first selective Pd -catalysed γ-C(sp )-H and γ-C(sp )-H arylation of free amino esters using a commercially available catalytic transient directing group. A variety of free amino esters, including α-amino esters and β-amino esters, amino monoesters and amino bis-esters, are shown to react with a diverse range of simple aryl and heteroaryl iodide reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 53 publications
0
54
0
Order By: Relevance
“…In 2018, Kamenecka and co‐workers reported Pd‐catalyzed γ‐C(sp 3 )−H and γ‐C(sp 2 )−H arylation of free amino esters using 2‐hydroxynicotinaldehyde ( L35 ) . It was found that the re‐esterification is necessary for this reaction due to the hydrolysis of the ester (Scheme ).…”
Section: Reversible Covalent Bonding For Transition Metal‐catalyzed Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Kamenecka and co‐workers reported Pd‐catalyzed γ‐C(sp 3 )−H and γ‐C(sp 2 )−H arylation of free amino esters using 2‐hydroxynicotinaldehyde ( L35 ) . It was found that the re‐esterification is necessary for this reaction due to the hydrolysis of the ester (Scheme ).…”
Section: Reversible Covalent Bonding For Transition Metal‐catalyzed Cmentioning
confidence: 99%
“…In 2018, Kamenecka and co-workers reported Pd-catalyzed g-C(sp 3 )ÀHa nd g-C(sp 2 )ÀHa rylation of free amino esters using 2-hydroxynicotinaldehyde (L35). [46] It was found that the reesterification is necessary for this reactiondue to the hydrolysis of the ester (Scheme 23). Interestingly,Y oung and co-workers presented as trategy using as toichiometrica mount of dry ice to provide CO 2 as al igand to mediate g-arylationo fa liphatic amines.…”
Section: )àHf Unctionalization Of Aminesmentioning
confidence: 99%
“…By applying the same aldehyde as transient directing group, Kamenecka further optimized this reaction for allylic and a-aromatic amino ester substrates and the g-(sp 3 )-and g-(sp 2 )-arylated products were obtained in decent yields (Scheme 21). 36 Instead of using aldehyde directly, Bull realized that simple a-oxylacetal can be applied as the directing aldehyde precursor in the g-arylation of aliphatic amines (Scheme 21). 37 Except for above examples where aldehydes (or their precursors) function in catalytic amount under the reaction conditions, stoichiometric amount of aldehyde, such as quinoline-8-carbaldehyde cat.…”
Section: Coupling Reactionmentioning
confidence: 99%
“…We also explored a glutamate ester, which gave the product with subsequent lactamization with the side chain after the arylation reaction (1ab) due to the transient nature of the DG. 43,44 A derivative of the dipeptide aspartame was also used in the reaction, in this case giving subsequent lactamization at the C-terminus (1ac). The reaction also worked on terpene-containing examples (1ad and 1ae), including a more complex cedrenecontaining cinnamylamine (1af).…”
mentioning
confidence: 99%